MotionDesigner: Augmented artistic performances with kinect-based human body motion tracking - Baptista, F.; Lopes, P. F.; Santana, P. (2016 23rd Portuguese Meeting on Computer Graphics and Interaction (EPCGI), 2016)
In the last two decades the use of technology in art projects has proliferated, as is the case of the interactive projections based on movement used in artistic performances and installations. However, the artists responsible for creating this work typically have to rely on computer experts to implement this type of interactive systems. The tool herein presented, MotionDesigner, intends to assist the design of these systems by providing artists with higher levels of autonomy and efficiency during the creative process, allowing them to specify the rules by which a human body interacts with both the audio and the visuals used in their interactive art work. The presented tool relies on an RGB-D camera to modulate the multimedia content according to the performer’s body motion. MotionDesigner is extensible so as to accommodate additions required by artists. The tool has been tested with dancers, choreographers, and architects. Results show that MotionDesigner is a valuable aid to artists, working as a catalyst of their creative process.